Immunomodulation‐Based Strategy for Improving Soft Tissue and Metal Implant Integration and Its Implications in the Development of Metal Soft Tissue Materials. (20th March 2020) - Liu, Runheng; Chen, Shoucheng; Huang, Peina; Liu, Guanqi; Luo, Pu; Li, Zhipeng; Xiao, Yin; Chen, Zhuofan; Chen, Zetao
Abstract: The difficulties associated with metal implants and soft tissue integration have significantly affected the applications of metal implants in soft‐tissue‐related areas. Prompted by the close association between soft tissue integration and the immune response, an immunomodulation‐based strategy is proposed to manipulate the immune microenvironment and improve metal implant–soft tissue integration. Considering their vital roles in soft tissue responses to metal implants, macrophages are used and the cytokines fingerprints of M1 and M2 macrophage immune microenvironments are evaluated for their potential modulatory effects on metal implant–soft tissue integration. The modulatory effects of different immune microenvironments on model soft tissue cells (human gingival epithelium cells) cultured on model metal implants (titanium alloy disks) are then described, with the underlying possible mechanism FAK‐AKT‐mTOR signaling unveiled. As further proof of concept, IL‐4/PDA (polydopamine)‐coated titanium alloy implants, aiming at modulating M2 macrophage polarization, are prepared and found to improve the in vivo metal implant‐soft tissue integration. It is the authors' ambition that this immunomodulation‐based strategy will change the negative perception and encourage the active development of metal materials with favorable soft tissue integration properties, thus improving the success rates of perforating metal implants and broadening their application in soft‐tissue‐related areas. Abstract : For the advancement of metal soft tissue materials, an immunomodulation‐based strategy is proposed to overcome the challenges of soft tissue and metal materials integration. The effects of macrophage‐mediated immune microenvironments on soft tissue and metal implant integration are unveiled. The M2 immune microenvironment is found to be more favorable for titanium alloy implant and epithelium tissue integration, possibly via activating the FAK‐AKT‐mTOR signaling.